ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK HANDPHONE MEREK SAMSUNG DI YOGYAKARTA - Tufiqiyah, Indria Dewi; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2015)
The purpose of this study is to determine whether the marketing mix of products, prices, distribution / place, and promotion influences the purchasing decision of Samsung brand mobile phone products. The sample used in this study amounted to 70 respondents, while the sampling method using purposive sampling. Data analysis method used is quantitative analysis with the validity and reliability tests, multiple linear regression, t test, F test, and the coefficient of determination. By using multiple methods it can be concluded that the product variable has a negative effect and is not significant to the purchase decision with a significance value (P Value) of 0.831> 0.05. While the price variable has a positive and significant effect on purchasing decisions with a significance value of 0.002 <0.05, and the distribution / place variable has a positive and not significant effect on a purchase decision with a significance value of 0.058> 0.05, and the promotion variable has a positive and significant effect on a purchase decision with a significance value 0.001 <0.05. The resulting determination coefficient is 0.629, which means that 62.9% of the change in the purchase decision variable is explained by the product, price, distribution / place and promotion variables together, while the remaining 37.1% is explained by other variables not included in this study.